Incorporating the patient voice in sarcoma research: How can we assess health-related quality of life in this heterogeneous group of patients? ; A study protocol - Hollander, Dide den; Fiore, Marco; Martin-Broto, Javier; Kasper, Bernd; Casado Herraez, Antonio; Kulis, Dagmara; Nixon, Ioanna; Sodergren, Samantha C.; Eichler, Martin; van Houdt, Winan J.; Desar, Ingrid M. E.; Ray-Coquard, Isabelle; et al. (Cancers, 2021)
Sarcomas comprise 1% of adult tumors and are very heterogeneous. Long-lasting and cumulative treatment side-effects detract from the (progression-free) survival benefit of treatment. Therefore, it is important to assess treatment effectiveness in terms of patient-reported outcomes (PROs), including health-related quality of life (HRQoL) as well. However, questionnaires capturing the unique issues of sarcoma patients are currently lacking. Given the heterogeneity of the disease, the development of such an instrument may be challenging. The study aims to (1) develop an exhaustive list of all HRQoL issues relevant to sarcoma patients and determine content validity; (2) determine a strategy for HRQoL measurement in sarcoma patients. We will conduct an international, multicenter, mixed-methods study (registered at clinicaltrials.gov: NCT04071704) among bone or soft tissue sarcoma patients ≥18 years, using EORTC Quality of Life Group questionnaire development guidelines. First, an exhaustive list of HRQoL issues will be generated, derived from literature and patient (n = 154) and healthcare professional (HCP) interviews (n = 30). Subsequently, another group of sarcoma patients (n = 475) and HCPs (n = 30) will be asked to rate and prioritize the issues. Responses will be analyzed by priority, prevalence and range of responses for each item. The outcome will be a framework for tailored HRQoL measurement in sarcoma patients, taking into account sociodemographic and clinical variables.